PENGARUH CAPITAL ADEQUACY RATIO, RETURN ON RISKED ASSETS, NON PERFORMANCE LOANDS DAN LOAN TO DEPOSIT RATIO TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Rina Masithoh Haryadi, Sandra Natalia Fransiska M, Imam Nazarudin Latif (EKONOMIA, 2021)
The purpose of this study was to determine the effect of Capital Adequacy Ratio, Return On Risked Assets Ratio, Non Performance Loands Ratio and Loan To Deposit Ratio on the stock prices of the banking sector during the 2015-2018 period, and to determine the effect of Capital Adequacy Ratio, Return On Risked Assets Ratio , Non Performance Loands Ratio, Loan To Deposit Ratio together (simultaneously) to the stock price of the banking sector during the period 2015-2018.The basic theory of this research consists of financial management, financial statements and ratio analysis of financial statements. Data collection techniques are carried out using secondary data taken from the Indonesian stock exchange www.idx.co.id. This research analysis tool uses multiple linear regression analysis.The results of this study include 1). Capital Adequacy Ratio (CAR) does not have a significant effect on stock prices. 2). The Return on Risked Assets Ratio (ROA) variable has no significant effect on stock prices. 3). The Non Performance Loands Ratio (NPL) variable does not significantly influence the stock price. 4). Variable Loan To Deposit Ratio (LDR) significantly influence stock prices. 5). Variable Capital Adequacy Ratio, Return On Risked Assets Ratio, Non Performance Loands Ratio, and Loan To Deposit Ratio together (simultaneously) significantly influence the stock prices of the banking sector during the 2015-2018 period